Ticzon herbal medicine encyclopedia - Ticzon, Romeo R. (Romeo R. Ticzon, publisher-author, 1996)
The first encyclopedia of the Philippine medicinal plants is due to the compilation of the eleven basic herbal manuals by well-known Filipino herbalists, botanists and pharmacist. By using simple layman's language, this book serves as a quick reference on the proper utilization, preparation and application of local herbs and plants with proven medicinal and curative values. It also summarizes herbal literature, medicinal properties of plants and the rich flora of our country.